Transforming Healthcare with Secure Cloud Infrastructure - Deneesh Narayanasamy (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The healthcare industry is experiencing a significant digital transformation through the adoption of cloud computing technologies. This article explores how secure cloud infrastructure supports innovations in healthcare delivery, including telemedicine, electronic health records (EHR), and AI-driven diagnostics. It examines the critical components of secure healthcare cloud infrastructure, focusing on identity management, data protection, and network security. The article presents case studies demonstrating successful cloud implementations in both large hospital networks and regional clinic settings, highlighting improvements in operational efficiency, patient care delivery, and cost management. Through analysis of current trends and future considerations, the article illustrates how emerging technologies like edge computing, blockchain, and the Internet of Medical Things (IoMT) are reshaping healthcare delivery while maintaining regulatory compliance and security standards.